2013
DOI: 10.1364/ol.38.003969
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopic ellipsometry on metal and metal-oxide multilayer hybrid plasmonic nanostructures

Abstract: The effective medium approximation is used to determine the optical constants of novel silver (Ag)/indium-tin oxide (ITO) multilayer nanopillar structures within the 300-800 nm wavelength range. The structures are modeled as inclusions in air with the pillar volume fraction at 42.4%, agreeing with SEM images of the sample. The simulated reflection intensity of the nanopillars is much less than that of the planar reference sample and is a result of the small difference between the refractive index of the top ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 17 publications
0
11
0
Order By: Relevance
“…Fabrication of imprinted nanopillar structures of polyacrylonitrile (PAN) with the desired pitch/aspect ratio and their characterization has been previously reported [6,36,37,38]. 1 cm × 1 cm ITO nanopillar electrodes were fabricated by depositing ITO on the previously nanoimprinted PAN structures, using an electron beam deposition technique.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Fabrication of imprinted nanopillar structures of polyacrylonitrile (PAN) with the desired pitch/aspect ratio and their characterization has been previously reported [6,36,37,38]. 1 cm × 1 cm ITO nanopillar electrodes were fabricated by depositing ITO on the previously nanoimprinted PAN structures, using an electron beam deposition technique.…”
Section: Resultsmentioning
confidence: 99%
“…The free carrier concentration of TCOs can be tuned under suitable doping and fabrication conditions by depositing a very thin layer of a noble metal (here Ag), with the effective metal carrier concentration variable through nanostructuring. The Maxwell-Garnett effective medium approximation was used to find the ratio of Ag and ITO in the core shell structures [37]. The bulk plasma frequency of Ag is 9.1 eV [54], however, depolarization charges due to the dielectric core cause a screened plasma frequency which is smaller than the bulk plasma frequency [55].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This is particularly useful for the nanostructured hybrid (Ag \ ITO) plasmonic electrodes we have reported earlier. Details of the ellipsometry study on these plasmonic electrodes with ITO shells has can be found in [15].…”
Section: Simulationmentioning
confidence: 99%
“…The ellipsometer offers the added advantage of obtaining phase information, thereby making it a powerful optical characterization technique [15] [16]. Different nanostructures such as split ring resonators [7], fishnet metamaterial [17] [18] etc. have been characterized using the method of ellipsometry.…”
Section: Introductionmentioning
confidence: 99%